Metastatic Non-Small Cell Lung Carcinoma treated with immunotherapy+ chemotherapy: a case of dissociated response? - Gigante, Ana Rita (2024)
Assessment of response to systemic therapy can be challenging in mNSCLC, especially with immunotherapy, due to the possibility of atypical response patterns. We report a case of metastatic lung adenocarcinoma under immunotherapy and chemotherapy with an apparent response dissociated in a pulmonary nodule, whose biopsy of the non-responsive lesion revealed a histological diagnosis different from the primary tumour. When there is a discrepancy in the type of response to systemic treatment of two different target lesions, it should be considered the possibility of a second primary tumour. The histopathological and/or molecular diagnosis confirmation is crucial for (re)staging, treatment decisions, and patient prognosis.